PEMANFAATAN LIMBAH KONSTRUKSI SEBAGAI AGREGAT HALUS BATAKO: HILIRISASI RISET DAN PENGUATAN MANAJEMEN BUMDES LALAYAAN - Steve W.M Supit; Sherley Runtunuwu; Raykes Tuerah; Heidy Pesik (Universitas Mataram, 2026)
BUMDes Lalayaan faces business and management problems. The brick printing equipment and mixer are not functioning, and the quality is not competitive, causing the business to fail. In addition, the administrators lack knowledge in managing BUMDes. The objective of this Community Service program is to provide solutions through equipment improvements and quality enhancements to concrete block mixtures in accordance with SNI standards, as well as to improve the social management of BUMDes. The activity method was carried out using participatory and community-based research, involving BUMDes managers and village officials in the entire activity process, from surveys to evaluations, conducted from July to November 2025 in Tatelu Village, North Minahasa Regency. By modifying the brick mixture using construction waste, BUMDes Lalayaan has produced innovative, environmentally friendly bricks that meet Indonesian National Standard specifications. This can increase competitiveness and support efforts to save the environment from unmanaged construction waste. The activities of repairing brick molding equipment and disseminating knowledge on brick manufacturing and financial management systems have increased the productivity of BUMDes through the knowledge and understanding of BUMDes administrators by 80%. Evaluation and assistance, including increased cooperation with third parties, can accelerate business development towards a more independent BUMDes Lalayaan in improving the welfare of the community in general.